Post-harvest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Post-harvest physiology and storage of tropical and subtropical fruits. Edited by S K Mitra. 1997. 423 pp. ISBN 0 85199 210 2. UK# 65. Publishing Division CAB International Wallingford Oxon, OX10 8DE UK. Fax: +44 1491 826090, Email: cabi-nao@